Difference of Serum MMP9 and TNF ???? Level in Preterm and Term Premature Rupture of Membranes - Wibowo, Aji P; Sulistyowati, Sri; Respati, Supriyadi H (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To examine the difference between matrix metalloproteinase‐ 9 (MMP‐9) and Tumor Necrosis Factor ???? (TNF‐????) serum levels in preterm and term premature rupture of membranes (PROM). Method: Our study employed an observational cross sectional approach. Seventy samples were divided into two groups, 35 samples with preterm PROM (28‐36 weeks gestational age) and 35 samples with PROM at term pregnancy (37‐42 weeks gestational age). Both groups underwent examination for serum MMP‐9 and TNF‐???? concentration using ELISA method. Statistical analysis was done using ttest. Result: Serum levels of MMP‐9 in the preterm PROM group was 2860.68K627.32 ng/ml, which was significantly higher than in the PROM at term pregnancy group 2549.74K657.15 ng/ml (p=0.04). Likewise, the average serum level of TNF‐???? in subjects with preterm PROM was 12,086.60K5384.51 ng/ml, significantly higher in comparison to PROM at term pregnancy, which was 6422.51K2645.32 ng/ml (p=0.00). Conclusion: Serum levels of MMP‐9 and TNF‐???? in preterm PROM is significantly higher than that in PROM at term pregnancy. Keywords: MMP‐9, premature rupture of membranes, preterm, term, TNF‐????